2022
DOI: 10.1177/21925682211053593
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Intelligence Approach to Predicting Unplanned Intubation Following Anterior Cervical Discectomy and Fusion

Abstract: Study Design Level III retrospective database study. Objectives The purpose of this study is to determine if machine learning algorithms are effective in predicting unplanned intubation following anterior cervical discectomy and fusion (ACDF). Methods The National Surgical Quality Initiative Program (NSQIP) was queried to select patients who had undergone ACDF. Machine learning analysis was conducted in Python and multivariate regression analysis was conducted in R. C-Statistics area under the curve (AUC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Previous retrospective studies reported that the incidence of postoperative reintubation after ACSS was 0.51%-1.0%. 1,[4][5][6][7][8][9] However, most previous reports only investigated patients undergoing ACSS for degenerative conditions such as cervical myelopathy and radiculopathy and have not included cervical spine injuries. In this series, all 3 patients who experienced reintubation were included in the trauma group; thus, no patients experienced reintubation in the nontrauma group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous retrospective studies reported that the incidence of postoperative reintubation after ACSS was 0.51%-1.0%. 1,[4][5][6][7][8][9] However, most previous reports only investigated patients undergoing ACSS for degenerative conditions such as cervical myelopathy and radiculopathy and have not included cervical spine injuries. In this series, all 3 patients who experienced reintubation were included in the trauma group; thus, no patients experienced reintubation in the nontrauma group.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Postoperative airway complication rates and unplanned reintubation after ACSS are 0.1%-6.6% and 0.51%-1.0%, respectively. 1,[4][5][6][7][8][9] Despite these low incidence rates, airway obstruction can lead to catastrophic complications and result in brain death or patient mortality.…”
mentioning
confidence: 99%
“…In addition to the previously mentioned errors, some papers provided poor calibration plots and omitted essential metrics. Kuris et al, Veeramani et al, and Zhang et al presented models predicting readmission, unplanned re-intubation, and short LOS, respectively, with acceptable AUROCs, accuracies, and BSs [16,27,29]. However, all three studies provided calibration plots indicating poor calibration, as the calibration curves were not in proximity to the near-perfect prediction diagonal.…”
Section: Other Errorsmentioning
confidence: 99%
“…
To the Editor, We read with great interest the study by Veeramani et al on artificial intelligence approaches to predict unplanned intubation after anterior cervical discectomy and fusion. 1 We agree that respiratory compromise can be devastating and that identification of high-risk patients is of paramount importance. We commend the authors for their efforts and wish to offer our insights.
…”
mentioning
confidence: 94%
“…Veeramani et al 1 are dealing with an imbalanced classification problem with only 283 real positive cases (.51%) and 54,219 real negative cases (99.49%). Thus, the focus during model development should be towards the positive class, as models will be inherently biased towards patients who did not require reintubation.…”
mentioning
confidence: 99%